Hak Janda Terhadap Harta Benda Dan Pengurusan Anak Dalam Budaya Kad’di Masyarakat Sabu - Bire, Chatryen M Dju; Manu, Ananda Natasya (Veteran Law Review, 2024)
In relation to marriage problems, when there is an event where the husband dies first, then culture Kad'di must be followed in the customs of the Sabu community. Culture Kad'di only done for those married to Sabu. Culture Kad'di done when the husband has been buried or a few days after being buried. When the wife returns to her clan of origin or returns to the lap of her parents and/or family, important matters arise, including child care and problems with assets. In the cultural Sabu indigenous people Kad'di have social values, cultural wisdom that is passed on (inherited) from one generation to another from generation to generation. The Savu people still maintain, maintain and treat culture Kad'di as customary law. Culture Kad'di which is carried out usually through a very long and cultured customary process that requires the right time, place and conditions.